Teachings of Rumi - Whinfield, E. H. (The Lost Library Glastonbury, 1987)
Whinfield's "The Teachings of Rumi" distills the essence of Rumi's poetic and philosophical teachings, highlighting the transformative power of love and the quest for spiritual enlightenment. The book delves into Rumi's understanding of the self, the divine, and the interconnectedness of all beings. Through a collection of Rumi's verses, Whinfield illustrates how love transcends boundaries, fosters compassion, and leads to a deeper understanding of one's place in the universe. The work invites readers to embrace the mystical journey of self-discovery and to recognize the sacredness of everyday experiences. Ultimately, Whinfield's interpretation serves as a guide for those seeking wisdom and inspiration from Rumi's timeless messages.